The Use of Modified Cervical Colar in Reducing Neck Pain - Zubaidi, Alfan; Fadli, Arif (Indonesian Journal of Medicine, 2021)
Background: One of the conditions of pain in the neck area where there is a stiff neck, so sometimes there is pain radiating from the shoulder to the hand, the symptom is often called cervical syndrome. This condition occurs because the vertebral root is compressed for a long time in the use of activities. In the long term, the pain can even radiate to both shoulders and even to the arms of the arch, this situation will result in abnormal and rapid fatigue. According to studies conducted by researchers, this situation may be prevented by giving a special cervical collar design to Tafidz Ouran students. In this study, it will be investigated how effective the special collar model is to overcome the problems/prevention of cervical syndrome for Tafidz Ouran students in Karanganyar. The purpose of this study was to determine how effective a special cervical collar design is to reduce pain in cervical syndrome.Subjects and Method: This research is a Randomized Controll Trial (RCT) where in this study before being randomized in determining the control and treatment groups, matching was done first. In the control group in this study were students who used regular collars (collars sold in the market) and in the intervention group were given special collars. The sample in this study was the students of the Tahfidz boarding school in the Karanganyar area as many as 160 students who experienced cervical syndrome. Each group in this study amounted to 80 students. The sampling technique was simple random sampling. The variables in this study, the dependent variable is the cervical syndrome condition of the Tafidz Quran students and the use of a special cervical collar model as the independent variable. Analysis of the data using the Independent samples t test if the data is normal, and using the Mann Whitney test if the data is not normal.Results: After the intervention, it was shown that pain in the special cervical collar group (mean = 2.51; SD = 0.50) was lower than that in the regular collar group (mean = 5.50; SD = 0.59) and was statistically significant (p value = 0.000).Conclusion: The use of a special cervical collar is better than a regular cervical collar to reduce neck pain.Keywords: cervical syndrome, cervical collar, special cervical collarCorrespondence: Alfan Zubaidi. Department of Orthotic Prosthetic, Ministry of Health Surakarta. Jl. Letjen Sutoyo, Mojosongo, Surakarta, Central Java, Indonesia. Email: drsalfanzubaidi@gmail.com.Indonesian Journal of Medicine (2021), 06(04): 460-464https://doi.org/10.26911/theijmed.2021.06.04.12